THE STRATEGIES USED BY ENGLISH TEACHER TO TEACH VOCABULARY AT GENTA ENGLISH COURSE PARE-KEDIRI - Saniyah, Dewi; Baehaki, Imam (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2021)
This study was aimed to find out the used of strategies used by English teacher to teach vocabulary. for those who are learning English, it is essential to learn about vocabulary mastery in order they can use it to communicate and to express their ideas, opinions, thoughts by using words, sentences, paragraphs through written form without having face to face with other people directly. The design of this research in qualitative descriptive. This research was conducted in Genta English course. The students were 10 students. It consist of 9 female and 1 male. To know the result of the student activity, the researcher used observation checklist, field note and interview. Teacher strategies in teaching vocabulary is the ways or steps that help learners to learning vocabulary by acting one of the strategies as steps formula, so that strategy become a facility which increasing learners understanding in learning vocabulary. It means use the strategies is good in teaching vocabulary.